EDITORIAL MESSAGE: Special Issue: Hydrogeology in Tunisia - Anis Chekirbane; Samia Khadhar; Soumaya Hajji; Imen Ayadi (Acque Sotterranee)
Water is the most critical resource in Tunisia, a country characterized by an arid to semi-arid climate along the Mediterranean Sea. With an irregular distribution of rainfall both spatially and temporally, Tunisia’s water resources are highly vulnerable to climate change. According to the Sixth Assessment Report (AR6) by the Intergovernmental Panel on Climate Change, water scarcity in the region is expected to intensify due to projected decrease in precipitation driven by global warming. [...]